2002
DOI: 10.1081/jfp-120015596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Physical Properties of Chicken Strips During Deep-Fat Frying

Abstract: Chicken slabs (10.061.060.5 cm) were deep-fat fried with sunflower oil at several temperatures 130, 140, and 150 C. Moisture content and oil absorption was determined during the whole experiment, and the following properties were evaluated: sample dimensions, temperature of the geometric center of the slab, mass transfer diffusivity, thermal diffusion coefficient and heat transfer coefficient. Fourier, Newton and Fick equations were applied to obtain the correspondent physical properties; whereas, empirical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The heat transfer coefficient values for other food products are 208–331 W/(m 2 K) for chicken strips (Velez‐Ruiz et al . ), 159–297 W/(m 2 K) for donuts (Velez‐Ruiz and Sosa‐Morales 2003) and 188–226 W/(m 2 K) for pork meat (Sosa‐Morales et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat transfer coefficient values for other food products are 208–331 W/(m 2 K) for chicken strips (Velez‐Ruiz et al . ), 159–297 W/(m 2 K) for donuts (Velez‐Ruiz and Sosa‐Morales 2003) and 188–226 W/(m 2 K) for pork meat (Sosa‐Morales et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…), chicken strips (Velez‐Ruiz et al . ), donuts (Velez‐Ruiz and Sosa‐Morales 2003), pork meat (Sosa‐Morales et al . ), potato slices (Yıldız et al .…”
Section: Introductionmentioning
confidence: 99%
“…The development of channels during heating increases the effective moisture diffusivity, facilitating the transport of water vapour from the interior of the sample to the surface 36. This implies that the effective diffusivity increases with increasing pore size 37. The larger pores in the sample made of 10 h milled flour resulted in a lower moisture content in the end of process.…”
Section: Resultsmentioning
confidence: 99%
“…Frying in shortening at 100 C Some authors have reported an increasing in oil content when the oil temperature was increased, such as Gamble, Rice, and Selman (1987) for potato slices, Moreira et al (1995) for tortilla chips and Vélez-Ruiz et al (2002) for chicken strips, but in the deep-fat frying of pork meat plates the increasing of fat content did not follow a direct relation respect to frying temperature. However, the frying medium type significantly affected the fat uptake (a = 0.05), occurring a lower fat absorption when shortening was used in the process.…”
Section: Mass Transfermentioning
confidence: 92%